2018
DOI: 10.1002/app.46573
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, optical, and thermal properties of polyimides containing flexible ether linkage

Abstract: The goal of this article was to synthesize a series of flexible polyimides containing ether linkage in main chain and clarified the effect of this ether linkage on some physical properties such as optical and thermal decomposition. Also, different functional group effects such as carbonyl (CO), hexa‐fluoro‐isopropylidene [C(CF3)2] and phenyl (C6H5) on these physical properties were evaluated. The structural characterization of poly(ether imide)s was performed using Fourier transform infrared, 1H‐nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Polyimide (PI) is an important type of high‐performance polymer. Due to the excellent thermal and mechanical properties, good electrical properties, and a series of outstanding performances under extreme conditions, aromatic PI films have attained much attention over the past decades, which have been used in optics, aerospace, and microelectronic fields . Recently, PIs were also used in synthesis of aerogel and got a noticeable ability of oil absorbance even in harsh environment and showed extraordinary potential in shape‐memory materials as well …”
Section: Introductionmentioning
confidence: 99%
“…Polyimide (PI) is an important type of high‐performance polymer. Due to the excellent thermal and mechanical properties, good electrical properties, and a series of outstanding performances under extreme conditions, aromatic PI films have attained much attention over the past decades, which have been used in optics, aerospace, and microelectronic fields . Recently, PIs were also used in synthesis of aerogel and got a noticeable ability of oil absorbance even in harsh environment and showed extraordinary potential in shape‐memory materials as well …”
Section: Introductionmentioning
confidence: 99%
“…These results clearly indicates that poly(azomethine‐imide)s bearing m‐ substituted aldehyde have higher than p‐ substituted aldehyde. It could be concluded properties of polymers that the presence of substitute azomethine (CN) linkage in the structure of polyimides were gained to higher thermal stability these polymers . As can be seen in Figure , the polymers have been generally showed two T g and loss modulus peaks in DMA curves.…”
Section: Resultsmentioning
confidence: 85%
“…It could be concluded properties of polymers that the presence of substitute azomethine ( C N) linkage in the structure of polyimides were gained to higher thermal stability these polymers. 29,30 As can be seen in Figure 7, the polymers have been generally showed two Tg and loss modulus peaks in DMA curves. Tan δ and loss modulus peaks at low temperature were attributed to the stiff glassy properties of the poly(azomethine-imide)s and at high peaks were associated with decomposition of the hydrogen bonding via Van der Waal's forces.…”
Section: Reflectance Spectra Of Poly(azomethine-imide)smentioning
confidence: 77%
“…Certainly, the incorporation of pyridine ring could also increase their solubility, which was due to the pyridine ring nitrogen atom in the structure produces a polarized bond and increases dipole–dipole interactions in the polymer–solvent system, further improving the polymer solubility. 30 Besides, their solubility was also affected by the rigidity of the used dianhydride monomers. For example, PEI- 6c and PEI- 6e are soluble in common organic solvents such as N -methyl-2-pyrrolidone, DMF, DMAc, and pyridine, even in low boiling point solvent like THF for PEI- 6e at room temperature because of the presence of the more flexible ether linkages and hexafluoroisopropylidene units, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…20 28 To our knowledge, although various colorless PIs have been reported in the last decade, it is still a challenge to develop new PIs with a combination of high T g , excellent optical transparency, good solubility, and high mechanical properties. It is well-known that the presence of flexible ether linkages into the molecular backbone presents the corresponding poly(ether imide)s (PEIs) 29,30 good solubility and processability, but some of their advantageous properties such as thermal stability and mechanical property were somewhat sacrificed. It has been demonstrated that the introduction of rigid heteroaromatic pyridine ring into the polymer main chains could endow it excellent thermal and thermooxidative stability, which is useful in decreasing the negative effects resulting from the incorporation of flexible linkages in the PI backbones.…”
Section: Introductionmentioning
confidence: 99%